Choose your destiny: Make a cell fate decision with COUP-TFII. Issue 157 (March 2016) - Wu, San-Pin; Yu, Cheng-Tai; Tsai, Sophia Y.; Tsai, Ming-Jer
Highlights: COUP-TFII is expressed in progenitor cells of multiple lineages. COUP-TFII controls major regulators of cell fate specification. This review focuses on the role of COUP-TFII in cardiovascular and renal systems. Abstract: Cell fate specification is a critical process to generate cells with a wide range of characteristics from stem and progenitor cells. Emerging evidence demonstrates that the orphan nuclear receptor COUP-TFII serves as a key regulator in determining the cell identity during embryonic development. The present review summarizes our current knowledge on molecular mechanisms by which COUP-TFII employs to define the cell fates, with special emphasis on cardiovascular and renal systems. These novel insights pave the road for future studies of regenerative medicine.